Internet-based student research : creating to learn with a step-by-step approach, grades 5-12 - Keane, Jacqueline P. (Linworth Pub., 2006)
Reproducible Internet-based student activity worksheets that teaches students in grades five through twelve how to use technology and the creative process in the learning experience.